MODEL PENGELOLAAN BISNIS SYARI’AH: Studi Kasus Lembaga Pengembangan Usaha Yayasan Badan Wakaf Sultan Agung Semarang - Choirul Huda (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Islamic business management becomes an interesting topic continues to increase. There are 3 (three) models of Islamic business management: 1) Sole proprietorships, 2) Partnership, and 3) Mudharaba with cooperation between two or more parties in which the owners of capital (shahibul mal) entrust amount of capital to the manager (muḍarib) with an agreement at the earliest. This paper analyze to the Islamic business management model developed by Lembaga Pengembangan Usaha (LPU) of Yayasan Badan Wakaf Sultan Agung (YBWSA) as a holding company that houses several business units. The types of business model is influence the applied business management model, and the type of business management model is influence the results of business operations. By using qualitative descriptive analysis, the study found that the LPU using multiple management models according to the type of business operation, which is a self-ownership (Takessa, Air Quasa, SA Radio), and partnerships (property, retail, Pumanisa), and combination model both self-ownership and partnerships (SApress, asset management and SAtour).